Synthesis of 3H, 2H4 and 14C‐SCH 417690 (Vicriviroc). (14th March 2016) - Hesk, D.; Borges, S.; Hendershot, S.; Koharski, D.; McNamara, P.; Ren, S.; Saluja, S.; Truong, V.; Voronin, K.
Abstract : Vicriviroc or SCH 417690 is a potent and selective antagonist of the CCR5 receptor. CCR5 receptor antagonists have the potential for the treatment of HIV infections. Four distinct isotopically labelled forms of SCH 417690 were synthesized. Low specific activity [ 3 H]SCH 417690 was prepared for a preliminary absorption, distribution, metabolism and excretion evaluation of the compound and [ 14 C]SCH 417690 for more definitive absorption, distribution, metabolism and excretion work, including an absorption, metabolism and excretion study in man. In addition, high specific activity [ 3 H]SCH 417690 was prepared for CCR5 receptor binding work and [ 2 H4 ]SCH 417690 was prepared as an internal standard for a liquid chromatography–mass spectrometry bioanalytical method. The paper discusses the synthesis of four isotopically labelled forms of SCH 417690. Abstract : Vicriviroc or SCH 417690 is a potent and selective antagonist of the CCR5 receptor. CCR5 receptor antagonists have the potential for the treatment of HIV infections. Four distinct isotopically labelled forms of SCH 417690 were synthesized.